Handbook of silicon based MEMS materials and technologies - Tilli, Markku (William Andrew is an imprint of Elsevier, 2015)
The Handbook of Silicon Based MEMS Materials and Technologies, Second Edition, is a comprehensive guide to MEMS materials, technologies, and manufacturing that examines the state-of-the-art with a particular emphasis on silicon as the most important starting material used in MEMS. The book explains the fundamentals, properties (mechanical, electrostatic, optical, etc.), materials selection, preparation, manufacturing, processing, system integration, measurement, and materials characterization techniques, sensors, and multi-scale modeling methods of MEMS structures, silicon crystals, and wafers, also covering micromachining technologies in MEMS and encapsulation of MEMS components. Furthermore, it provides vital packaging technologies and process knowledge for silicon direct bonding, anodic bonding, glass frit bonding, and related techniques, shows how to protect devices from the environment, and provides tactics to decrease package size for a dramatic reduction in costs.
Keywords: Microelectromechanical systems.; Microelectromechanical systems -- Materials.; Silicon -- Electric properties.; elektronické knihy; electronic books